2016
DOI: 10.18632/oncotarget.12860
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear transcription factor Nrf2 suppresses prostate cancer cells growth and migration through upregulating ferroportin

Abstract: VTo investigate the effect of nuclear transcription factor Nrf2 on the transcription of Ferroportin (FPN) in prostate cancer cells, and the regulation mechanisms of FPN on cell viability, migration and apoptosis of prostate cancer cells.Empty vectors, pEGFPC1-Nrf2, pEGFPC1-FPN, Si-FPN and Si-Nrf2 were transfected into prostate cancer cell line PC3. The expression of mRNA and protein were measured by real time-PCR (RT-PCR) and western blot. Cell viability, migration, cycle and apoptosis were tested by CCK-8 ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 36 publications
0
34
0
Order By: Relevance
“…Moreover, AMPK and SIRT1 can regulate transcription factors, such as Nrf2 and NF-κB, which are involved in regulating antioxidant genes against oxidative damage and the suppression of pro-inflammatory cytokines, respectively [39,40,42]. Nrf2, which is an essential transcription factor for expression of antioxidant genes, is another important modulator of the intracellular adaptive antioxidant response to oxidative stress [33,34]. Nrf2 binds to specific DNA sequence antioxidant responsive element (ARE) and stimulates the transcription of downstream target genes, antioxidant genes, including CAT, SOD, and GPX.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, AMPK and SIRT1 can regulate transcription factors, such as Nrf2 and NF-κB, which are involved in regulating antioxidant genes against oxidative damage and the suppression of pro-inflammatory cytokines, respectively [39,40,42]. Nrf2, which is an essential transcription factor for expression of antioxidant genes, is another important modulator of the intracellular adaptive antioxidant response to oxidative stress [33,34]. Nrf2 binds to specific DNA sequence antioxidant responsive element (ARE) and stimulates the transcription of downstream target genes, antioxidant genes, including CAT, SOD, and GPX.…”
Section: Discussionmentioning
confidence: 99%
“…The inhibition of CYP2E1 activity has been shown to result in successful recovery of ethanol-induced fatty liver [32]. Nuclear factor E2-related factor 2 (Nrf2) is another important regulator of the intracellular adaptive antioxidant response to oxidative stress [33][34][35]. In addition, alcohol exposure is shown to induce hepatic lipid accumulation in Nrf2-null mice [36], and the activation of Nrf2 was able to successfully prevent alcohol-induced fatty liver [37].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that resveratrol exerts potent anti-initiation, anti-promotion and antiprogression activities throughout the multi-stage process of carcinogenesis (153). Resveratrol can augment cellular antioxidant defence capacity and sensitise prostate cancer cells to treatment through reducing both undesired basal reactive oxygen species (ROS) and reactive nitrogen species (RNS) as well as inducing antioxidant enzymes such as heme-oxygenase-1 (HO-1) through ARE-mediated transcriptional activation of Nrf2 (156)(157)(158). In addition to its inhibition of COX-2 expression, resveratrol has been found to interfere with proinflammatory signalling pathways triggered by IL1-β leading to inhibition of inflammation, which is often involved in cancer onset and progression by regulating proliferation, apoptotic cell death and angiogenesis (159).…”
Section: Resveratrolmentioning
confidence: 99%
“…A well-established YAP role on physiological cellular behavior, is its action on cell migration which is related in oncology field to the invasion and the metastatic capability of tumor cells [30][31][32]. In addition, some data indicated that Nrf2 suppression also reduced the migration in different tumor cells [33][34]. To verify whether the reduction of YAP and/or Nrf2 expressions could reduce cell migration, we analyzed this parameter through the wound healing method in Nrf2 silenced, YAP knocked down cells and in cells silenced for both genes (Fig.…”
Section: The Reduction Of Nrf2 Expression Was Analyzed In 253j C-r 2mentioning
confidence: 99%